2021
DOI: 10.1038/s41598-021-98147-w
|View full text |Cite
|
Sign up to set email alerts
|

Revealing semantic and emotional structure of suicide notes with cognitive network science

Abstract: Understanding how people who commit suicide perceive their cognitive states and emotions represents an important open scientific challenge. We build upon cognitive network science, psycholinguistics and semantic frame theory to introduce a network representation of suicidal ideation as expressed in multiple suicide notes. By reconstructing the knowledge structure of such notes, we reveal interconnections between the ideas and emotional states of people who committed suicide through an analysis of emotional bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 65 publications
2
34
0
Order By: Relevance
“…The authors identified a strong polarisation in favour and against humanitarian interventions to immigration mainly correlated with political factions, in agreement with previous social network approaches 34 . Teixeira and colleagues 49 used semantic/syntactic networks to reconstruct stances expressed in suicide notes and found negative perceptions of concepts like “love”, distorted by suicide ideation when compared to control data. Mokryn and colleagues found that the emotional words expressed in movie reviews were predictive of the emotions inspired by those movies, further strengthening a connection between textual data and cognitive/emotional content.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors identified a strong polarisation in favour and against humanitarian interventions to immigration mainly correlated with political factions, in agreement with previous social network approaches 34 . Teixeira and colleagues 49 used semantic/syntactic networks to reconstruct stances expressed in suicide notes and found negative perceptions of concepts like “love”, distorted by suicide ideation when compared to control data. Mokryn and colleagues found that the emotional words expressed in movie reviews were predictive of the emotions inspired by those movies, further strengthening a connection between textual data and cognitive/emotional content.…”
Section: Related Workmentioning
confidence: 99%
“…Through the lens of cognitive network science 12 , 16 , 40 , discourse content, centrality and frames can all be measured via interpretable network metrics and, importantly, visualised. These aspects provide experimenters direct access into the structure of stances expressed in texts 45 and also in the psychology of text authors 46 , 49 . A key advantage of TFMNs is their ability to unveil semantic frames surrounding specific concepts in discourse as network neighbourhoods of concept associations.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, to detect sentiment and emotions around aspects "gender" and "gap" in 10,000 tweets, Stella [16] used a multi-layer perceptron to extract syntactic structure information and build a network of non-stopwords. Similarly, to investigate sentiments and emotions around aspects "love" and "live" in suicide notes, Sofia [17] used syntactic structure information to construct subject-verb-object triads.…”
Section: Related Workmentioning
confidence: 99%
“…Communication materials like texts are an open view to the mindset of the authors, which is a proxy for the structure of language and its associations in the human mind (Teixeira et al, 2021).…”
Section: From Words To Mindset Reconstruction With Forma Mentis Networkmentioning
confidence: 99%